KEBIJAKAN PENGUASA DALAM PELESTARIAN BANGUNAN KEAGAMAAN PADA MASA PEMERINTAHAN RAKAI WATUKURA DYAḤ BALITUNG (898-910 M.) - Yogi Pradana (Badan Riset dan Inovasi Nasional, 2017)
Abstract. Policy of the Authorities in the Preservation of Religious Buildings During the Reign of Rakai Watukura Dyaḥ Balitung (898-910 A.D.) This study discusses the policy of the authorities during the reign of King Balitung (898-910 A.D.) of Ancient Mataram Kingdom. The policy that was discussed in this study was the forms of preservation of religious buildings. The aim of this study was to provide information on the forms of preservation of religious buildings in the past. The method used in this study was inductive reasoning with descriptive-analytic approach. The analysis used in this study was structural analysis, which was making internal critic on inscriptions’ transliterations to generate interpretation about aspects of human life. Based on this study, it is known that the mention of the religious buildings’ preservation policy is expressed explicitly or implicitly, while the forms of policies to preserve religious buildings were among others renovation, addition of buildings, and maintenance. Keywords: Policy, Preservation, Religious buildings, Inscription Abstrak. Penelitian ini membahas kebijakan penguasa pada masa pemerintahan Raja Balitung (898-901 Masehi) dari Kerajaan Mataram Kuno. Kebijakan yang dibahas bentuk pelestarian bangunan keagamaan berdasarkan data prasasti dari masa pemerintahan Raja Balitung. Penelitian ini bertujuan untuk mencari bentuk pelestarian bangunan keagamaan pada masa lampau. Metode yang digunakan adalah penalaran induktif dengan sifat deskriptif-analitis. Analisis yang digunakan dalam penelitian ini berupa analisis struktural, yaitu melakukan kritik intern pada transliterasi atau alih bahasa isi prasasti untuk memperoleh penafsiran berupa aspek-kehidupan manusia. Berdasarkan penelitian diketahui bahwa penyebutan kebijakan pelestarian bangunan keagamaan dalam prasasti disebutkan, baik secara tersurat maupun tersirat. Adapun bentuk-bentuk kebijakan penguasa dalam melestarikan bangunan keagamaan antara lain berupa renovasi, penambahan bangunan, dan perawatan bangunan. Kata Kunci: Kebijakan, Pelestarian, Bangunan keagamaan, Prasasti